Cognitive behavioural therapy for psychosis prevention: a systematic review and meta-analysis. Issue 3 (22nd March 2013) - Hutton, P.; Taylor, P. J.
Abstract : Background: Clinical equipoise regarding preventative treatments for psychosis has encouraged the development and evaluation of psychosocial treatments, such as cognitive behavioural therapy (CBT). Method: A systematic review and meta-analysis was conducted, examining the evidence for the effectiveness of CBT-informed treatment for preventing psychosis in people who are not taking antipsychotic medication, when compared to usual or non-specific control treatment. Included studies had to meet basic quality criteria, such as concealed and random allocation to treatment groups. Results: Our search produced 1940 titles, out of which we found seven completed trials (six published). The relative risk (RR) of developing psychosis was reduced by more than 50% for those receiving CBT at every time point [RR at 6 months 0.47, 95% confidence interval (CI) 0.27–0.82, p = 0.008 (fixed-effects only: six randomized controlled trials (RCTs), n = 800); RR at 12 months 0.45, 95% CI 0.28–0.73, p = 0.001 (six RCTs, n = 800); RR at 18–24 months 0.41, 95% CI 0.23–0.72, p = 0.002 (four RCTs, n = 452)]. Heterogeneity was low in every analysis and the results were largely robust to the risk of an unpublished 12-month study having unfavourable results. CBT was also associated with reduced subthreshold symptoms at 12 months, but not at 6 or 18–24 months. No effects on functioning, symptom-related distress or quality of life were observed. CBT was not associated with increased rates of clinical depression or social anxiety (two studies). Conclusions: CBT-informed treatment is associated with a reduced risk of transition to psychosis at 6, 12 and 18–24 months, and reduced symptoms at 12 months. Methodological limitations and recommendations for trial reporting are discussed.